Peran Motivasi Terhadap Produktivitas Karyawan (Literature Review) - Ajijah, Anisa Hasna Nur; Khoerunnisa, Yulia; Hidayanto, Dwi Kurnia; Rosid, Rosid (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
Competition has raised various threats related to how a company operates and survives in the industrial world, until finally through various innovations and creativity it is shown as an important role in implementing what the company thinks and plans to achieve the success that the company expects, both from product innovation to operational innovation. ensure innovation in the effectiveness of its performance. Therefore, it is important for companies to develop innovations, especially in employee relations as part of their operations so that for this the company creates a new field called the field of human resources (HR), namely work activities that ensure the performance of employees in the company operates well and supports and improves productivity. In this case, the HR field at the company found that it was the employee's self-motivation that could support success in a practice of increasing productivity and increasing or decreasing performance. In writing this article aims to determine the various factors that generate employee morale as an influence on the productivity of their performance to achieve company goals. The method used in the collection of journals using google schooler published from 2015-2021. The result of this literature review is the identification of various motivating factors for employee motivation, namely internal and external factors or motivation that comes from within and outside the employee himself as an effort to fulfill life satisfaction in his work.